1994
DOI: 10.1016/0014-5793(94)01261-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of defensin binding to C1 complement

Abstract: In human serum we found strong defensin binding to the complexes of activated Cl complement (CT) and Cl inhibitor (Cli). Purified Clq, activated Cl tetrame_r (T&) and Cli did not bind defensin. When f& was dissociated by EDTA, only the activated Cls (Cls) bound defensin. Binding of defensins to Cl complement represents a newly recognized bridge between the complement-and phagocyte-mediated host defenses, and a potential mechanism for protecting infected tissue from cytotoxic injury by defensin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Defensins have been shown to bind to ␣ 2 -macroglobulin (30), serpins (31), and C1q (32). Despite the formation of these complexes, the plasma concentration of defensins is only 50 ng/ml in healthy subjects (33) and thus very low in comparison with the levels of defensins in neutrophils.…”
Section: Discussionmentioning
confidence: 97%
“…Defensins have been shown to bind to ␣ 2 -macroglobulin (30), serpins (31), and C1q (32). Despite the formation of these complexes, the plasma concentration of defensins is only 50 ng/ml in healthy subjects (33) and thus very low in comparison with the levels of defensins in neutrophils.…”
Section: Discussionmentioning
confidence: 97%
“…For example, it has been shown that human ␣-defensins, HNP 1-3, are bound by activated ␣ 2 -macroglobulin (29), and by several other serum proteins, including C1q, ␣ 1 -proteinase inhibitor, ␣ 1 -antichymotrypsin, ␣ 2 -antiplasmin, and antithrombin III (30,31). It remains to be determined whether these defensins bind to glycan moieties, or whether any of the proteins also bind -defensins.…”
Section: Discussionmentioning
confidence: 99%
“…Human α-and β-defensins are inactivated by serum components and higher NaCl concentrations [86,87], which also is the case for porcine pBD-1 [105]. However, protegrins maintain their activities in the presence of cations, serum or at physiological NaCl concentrations in vitro [52].…”
Section: Synergistic Interactions Among Porcine Ampsmentioning
confidence: 99%